The emotional facial recognition performance of Chinese patients with schizophrenia: An event-related potentials study - Yangjun Zhang; Ding Zhao; Jianfan Wu; Lixin Lin; Jiawu Ji (Indian Journal of Psychiatry)
Background: Patients with schizophrenia have deficits in identifying and recognizing emotional facial expressions. Aim: This study aimed to explore the event-related potential (ERP) responses of patients with schizophrenia (SZ) and healthy controls (HC) using the Chinese Facial Affective Picture System (CFAPS). Methods: This study included 30 SZs and 31 HCs. We asked them to complete the task based on the oddball paradigm, in which three emotional faces (happy, fearful, and neutral) were used as target stimuli. Additionally, the amplitude and latency of the N170 component and the P300 component were recorded synchronously. Results: Compared with HCs, SZs had significantly smaller amplitudes of N170 and P300 to all facial expressions. The pairwise comparison revealed that fearful faces could trigger a significantly larger P300 amplitude in HCs than neutral faces, while the such a difference was not found in SZs. Conclusion: These findings indicated that SZs had a noticeable deficiency in the structural coding of face recognition and available attentional resources.